2008
DOI: 10.1128/iai.00647-07
|View full text |Cite
|
Sign up to set email alerts
|

Anamnestic Protective Immunity to Bacillus anthracis Is Antibody Mediated but Independent of Complement and Fc Receptors

Abstract: The threat of bioterrorist use of Bacillus anthracis has focused urgent attention on the efficacy and mechanisms of protective immunity induced by available vaccines. However, the mechanisms of infection-induced immunity have been less well studied and defined. We used a combination of complement depletion along with immunodeficient mice and adoptive transfer approaches to determine the mechanisms of infection-induced protective immunity to B. anthracis. B-or T-cell-deficient mice lacked the complete anamnesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…Nor do oligoclonal mixtures of non-neutralizing mAbs provide any degree of protection (A. Yermakova and N. Mantis, unpublished results). This is in contrast to what has been observed in the case of BoNT where Fc receptor-mediated clearance is important in counteracting high-dose toxin exposure (Nowakowski et al, 2002; Sepulveda et al, 2010) and in the case of anthrax toxin where protection is modulated by IgG subclass and FcγR utilization (Abboud et al, 2010; Harvill et al, 2008; Mabry et al, 2005; Maynard et al, 2002; Wild et al, 2003). …”
contrasting
confidence: 73%
“…Nor do oligoclonal mixtures of non-neutralizing mAbs provide any degree of protection (A. Yermakova and N. Mantis, unpublished results). This is in contrast to what has been observed in the case of BoNT where Fc receptor-mediated clearance is important in counteracting high-dose toxin exposure (Nowakowski et al, 2002; Sepulveda et al, 2010) and in the case of anthrax toxin where protection is modulated by IgG subclass and FcγR utilization (Abboud et al, 2010; Harvill et al, 2008; Mabry et al, 2005; Maynard et al, 2002; Wild et al, 2003). …”
contrasting
confidence: 73%
“…Hence, each mechanism is currently thought to depend only on the interaction of antibody and toxin. Consistent with this notion, several studies have shown that protection against an anthrax challenge is based on antibody-neutralizing toxin components and that Fab fragments of antibodies induced by vaccination are sufficient for protection (Maynard et al, 2002;Wild et al, 2003;Laffly et al, 2005;Mabry et al, 2005;Harvill et al, 2008). These findings can be interpreted as indicating that neither FcR binding nor the Fc domain is essential for toxin neutralization.…”
mentioning
confidence: 79%
“…In vitro binding assays show that the monoclonal antibody inhibits protective antigen interaction with cellular receptors, which prevents toxin-mediated killing and confers protection from lethal challenge in vivo 83,84 . Furthermore, passive transfer studies of the Fab domain 85 in mice deficient in T cells, B cells, complement or FcRs have suggested that Fab domain binding to protective antigens alone is sufficient to confer protection, without activation of downstream Fc domain effector functions 86 . However, the Fc domain does still have a significant impact.…”
Section: Antibody-mediated Effector Functionsmentioning
confidence: 99%